The Relationship Between Dust Quality and Home Ventilation with the Incidence of Upper Respiratory Tract Infection (URI) in The Ex-place of Final Processing (TPA) Keputih - Lailatul Fitriyah (Universitas Airlangga, 2016)
Abstract: Upper Respiratory Track Infections (URI) is a kind of respiratory disease which is closely related to the quality of housing and the quality of ambient air. Ventilation is one component of a residential environmental health assessment. The dust may cause dryness of mucous in the respiratory tract so that a person may suffer or feel the symptoms of respiratory infection. This study aimed to analyze the relationship between ambient air dust and ventilation in the former place of fi nal processing (TPA) Keputih with URI (Upper Respiratory Tract Infection). This research is a cross sectional analytical and observational. The sample in this study is the ambient air concentration of dust particles and housewives from 77 families in RW VIII Keputih Area. To determine the relationship of ambient air dust and ventilation with respiratorydisease using Chi Square test. The results showed that respondents who had experienced respiratory infection as much as 89,6%. Levels of dust particles measured at the point I exceeded the quality standard that is equal to 0,3223 mg/Nm3. Home ventilation that do not appropiate the requirements of a healthy home is at 93.5%.There's a relationship between the use of home ventilation with URI (p = 0.000) and the levels of ambient air dust particles with URI (p = 0.003). This study concludes that the two variables associated with the incidence of respiratory infection so the need for community empowerment and proactive attitude of the various instruments of government in the area of research on the prevention of URI and the presence of a good control of the quality of environmental health VIII RW Keputih Area.Keywords: dust quality, home ventilation, the ex-place of fi nal processing, URI